The nexus between FDI and external balance of selected Emerging European Economies – a panel data approach - Dajana Ercegovac; Emilija Beker Pucar (Anali Ekonomskog fakulteta u Subotici, 2022)
Abstract: This research focuses the nexus between foreign direct investments (FDI) and external balance in selected Emerging European Economies (EEEs). Emerging countries in convergence process tend to have problem of structural external imbalance that is covered with foreign capital inflows. FDI are long-term and sustainable source of financing the current account deficit. The aim of this paper is to test if FDI together with chosen macroeconomic indicators are relevant factors of trading balance in EEEs in order to give useful implications towards economic policy creators in emerging economies. Research hypothesis is tested with robust micro panel models for total sample and two subperiods: before and after the structural break caused with Global financial crisis (GFC). The results indicate that substantial FDI inflows are significantly related with negative sum of trading balance on the total sample level i.e. average external position deficit is financed with the FDI inflows. Also, dummy variable for the Western Balkans indicates that FDI are significant variable that finances external imbalance in this subsample. The government policy recommendations are directed towards incentive measures for attracting greater FDI inflows, especially greenfield investments motivated with greater efficiency and export stimulation in order to stabilize trading balance and foster economic growth.